Sea ice directs changes in bowhead whale phenology through the Bering Strait - Angela R. Szesciorka; Kathleen M. Stafford (Movement Ecology, 2023)
Abstract Background Climate change is warming the Arctic faster than the rest of the planet. Shifts in whale migration timing have been linked to climate change in temperate and sub-Arctic regions, and evidence suggests Bering–Chukchi–Beaufort (BCB) bowhead whales (Balaena mysticetus) might be overwintering in the Canadian Beaufort Sea. Methods We used an 11-year timeseries (spanning 2009–2021) of BCB bowhead whale presence in the southern Chukchi Sea (inferred from passive acoustic monitoring) to explore relationships between migration timing and sea ice in the Chukchi and Bering Seas. Results Fall southward migration into the Bering Strait was delayed in years with less mean October Chukchi Sea ice area and earlier in years with greater sea ice area (p = 0.04, r2 = 0.40). Greater mean October–December Bering Sea ice area resulted in longer absences between whales migrating south in the fall and north in the spring (p < 0.01, r2 = 0.85). A stepwise shift after 2012–2013 shows some whales are remaining in southern Chukchi Sea rather than moving through the Bering Strait and into the northwestern Bering Sea for the winter. Spring northward migration into the southern Chukchi Sea was earlier in years with less mean January–March Chukchi Sea ice area and delayed in years with greater sea ice area (p < 0.01, r2 = 0.82). Conclusions As sea ice continues to decline, northward spring-time migration could shift earlier or more bowhead whales may overwinter at summer feeding grounds. Changes to bowhead whale migration could increase the overlap with ships and impact Indigenous communities that rely on bowhead whales for nutritional and cultural subsistence.